Secondary Abutment Syndromes of the Wrist in Trauma: A Pictorial Essay - Mespreuve, Marc; Waked, Karl; Verstraete, Koenraad (Journal of the Belgian Society of Radiology, 2018)
Traumatic lesions of the wrist occur frequently and may give rise to underdiagnosed secondary abutment syndromes. The latter are a common cause of incapacitating pain and limited range of motion, despite minimal or even absent alterations on radiographs. Moreover, the complex wrist anatomy often results in ignorance or underappreciation of these syndromes. This paper presents a pictorial review of frequent and rare secondary abutment syndromes at the wrist joint, which - in contrast to primary abutment syndromes - are not based on anatomical variants or congenital deformations. The merit of each imaging modality is briefly mentioned.